Stališča študentov Pedagoške fakultete Univerze v Ljubljani do slovenščine kot učnega jezika - Skubic, Darja (Revija za elementarno izobraževanje, 2013)
Attitudes of Students at the Faculty of Education, University of Ljubljana, Towards Slovenian as the Language of Instruction. The paper discusses the Slovenian language as the language of instruction in higher education context. First, the status of Slovenian throughout history is briefly described. Second, the author points out the role of the Slovenian standard language in the educational system from kindergarten to the university, and the full functional role of the Slovenian language within higher education, i.e. Slovenian as the academic language in different disciplines. Further, the paper provides an outline of language guidelines as included in various documents, such as The Country Profile of Slovenia (2003), The National Programme for Language Policy (2007-2011), The White Paper (2011), The Common European Framework for Languages (2001), and the draft of the National Programme for Language Policy 2012-2016. The empirical part focuses on a survey, which investigated into the attitudes of students at the Faculty of Education towards Slovenian as the language of instruction. The conclusions drawn from the survey suggest some strategies for improving the current language practice in the higher education context.
Keywords: Slovenian as the language of instruction; higher education; Slovenian language policy